The effect of extended early rehabilitation on the treatment outcome of patients with moderate and severe traumatic brain injury - Keleman, Nataša; Dragičević-Cvjetković, Dragana; Mikov, Aleksandra; Radošević, Dragomir; Ðilvesi, Ðula; Mrđa, Vladimir; Krasnik, Rastislava (Frontiers in Human Neuroscience, 2025)
IntroductionTraumatic brain injury (TBI) is one of the leading causes of morbidity, disability and mortality in all age groups. The functional disability left by TBI, is significant for the patient, family and society. Treatment and early rehabilitation are crucial to the overall level of recovery.ObjectiveTo compare the impact of extended early rehabilitation of patients with moderate and severe traumatic brain injury on the outcome of treatment.MaterialA prospective experimental study comprised 124 patients with moderate and severe TBI, randomly divided into two groups. The patients of the experimental group had kinesitherapy seven days a week, twice a day for 45 min, and the patients of the control group had kinesitherapy seven days a week, twice a day for 30 min. The follow-up parameters were: age, sex, mechanism of injury, associated injuries, comorbidities, Glasgow Coma Scale (GCS) on admission and discharge, early rehabilitation interruptions, presence of tracheostomy, decubitus ulcers, nasogastric tube, diapers and urinary catheter at the discharge from the Intensive Care Unit and discharge from the hospital, and mortality.Results124 patients were randomly divided into two groups of 62 patients each. The male gender dominated 95 (76.6%). The average age was Me = 62.00 (IQR = 36.0) years. There was no statistically significant difference between the groups in gender, age, mechanism of injury, associated injuries and comorbidities. GCS on admission; 68 (54.8%) patients had severe, 56 (46.2%) moderate TBI, at discharge: 22 (17.7%) had severe, 11 (8.9%) moderate and 91 (73.4%) mild TBI. At discharge from the ICU, the presence of tracheostomy was (13 vs. 19), (p = 0.218), nasogastric tube (33 vs. 45), (p = 0.026) and decubitus ulcers (0 vs. 4), (p = 0.042) were less in the experimental group. At discharge from the hospital, tracheostomy (6 vs. 16), (p = 0.019), urinary catheter (38 vs. 48), (p = 0.051), diapers (29 vs. 40), (p = 0.047) were less in the experimental group. There were 5 deaths in both groups. There was no statistically significant difference in early rehabilitation interruptions between groups (5 vs. 6).ConclusionExtended early TBI rehabilitation is safe, effective and contributes to a positive outcome of treatment.